The ancient world at war a global history - De Souza, Philip (Thames & Hudson, 2008)
A global history of ancient warfare, covering Egypt, the Near East, Greece, Rome, Central Asia, India, China, Korea, Japan, and the Americas. In this new survey of ancient warfare, a group of distinguished historians and archaeologists discusses major battles and wars from around the world. The book ranges in time from 8000 BC and the earliest evidence of warfare in northern Iraq to the armies of the Aztecs and Incas half a millennium ago, and includes Alexander the Great's triumphant campaigns against Persia in the fourth century BC, Caesar's Gallic Wars, the Han Chinese defeat of the nomadic Xiongnu horsemen, and the Inca ruler Atahualpa's last stand against Pizarro. The authors combine descriptions of the course of military events with expert analyses and explanations of the underlying social, economic, and cultural factors that shaped ancient warfare. Their essays survey the evolution of armies, tactics, and military equipment, from the strategic mastery evident in an early Chinese treatise on war by Sunzi to the rise of the Greek hoplite warrior and the development of swords and armor in ancient Japan. Special features cover key battles such as Qadesh, Issus, and Cannae; weaponry from shields to artillery; and visual resources such as Trajan's Column and the Terracotta Army. The rich illustrative material includes photographs, drawings, and specially commissioned 3-D battle reconstructions, maps, and plans. 351 illustrations, 150 in color. Contributions by: Elizabeth Arkush; Gina Barnes; Brian S. Bauer ; Daniel Boatright; Robin Coningham; Jon Coulston; Hugh Elton; R. Brian Ferguson ; Ross Hassig; Mark Manuel; Alan Peatfield; Charles A. Peterson; David Potter; Louis Rawlings; Nathan Rosenstein; Nicholas Sekunda; Ian Shaw; Joe Szymczak; Nigel Tallis; Hans van Wees.